Seasonal affective disorder practice and research (Oxford Univ. Press, 2010)
Seasonal affective disorder(SAD), or winter depression, is a mood disorder related to the change in the seasons and lack of exposure to daylight. It affects 1 in 100 adults in western countries. SAD is a rare example of a psychiatric disorder with a clear, identifiable biological cause. This book presents an evidence-based review of our understanding of SAD, focusing on clinical aspects as well as research issues. After a short review of the history of the condition, the first part of the book is clinical in emphasis, covering the presentation of the condition and its symptoms, the epidemiology, and the various options for treatment. Part two shifts the focus to examine research into SAD, covering the range of hypotheses put forward to explain the cause of the condition, and reviewing the experimental evidence for each theory.